PENDIDIKAN KARAKTER DALAM PELAKSANAAN PEMBELAJARAN SENI TARI DI SEKOLAH DASAR NEGERI 20 GUMARANG - Rahma Taher (STKIP Subang, 2023)
This study aims to analyze the implementation of character education in dance learning at SD Negeri 20 Gumarang. Character education has an important role in shaping students' personality and morality, and dance can be an effective means of developing that character. The research method used in this study is a qualitative approach using observation techniques, interviews, and documentation studies. The research subjects consisted of dance teachers and lower grade students at SD Negeri 20 Gumarang. The results of the study show that character education has been integrated effectively into dance learning at the school. Dance teachers use character values such as cooperation, discipline, creativity, honesty, and responsibility in every learning activity. They also use examples from everyday life to relate character values to dance practice. In addition, this study also revealed that students showed positive changes in their character development through learning the art of dance. They learn to work together in groups, respect the opinions of others, appreciate cultural diversity through dance moves, and develop a sense of responsibility towards their duties and obligations. In conclusion, learning the art of dance at SD Negeri 20 Gumarang has succeeded in implementing character education well. The dance teacher acts as an effective facilitator in integrating character values into learning, while students show positive progress in developing character through the practice of dance. This research provides a better understanding of the importance of character education through dance at the elementary education level.